2007
DOI: 10.1007/s10832-007-9114-6
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature sintering and microwave dielectric properties of Mg4Nb2O9 ceramics

Abstract: The effects of V 2 O 5 and Li 2 CO 3 on the sinterability and microwave dielectric properties of Mg 4 Nb 2 O 9 (MN) ceramics were investigated. With addition of 1.5wt% V 2 O 5 , the dielectric constant (e) and Q · ƒ value of MN ceramics sintered at 1,000°C are comparable to those of pure MN sintered at 1,400°C. The good results are because of the enhancement of the density by liquid sintering at the lower temperatures. With the mixtures of V 2 O 5 and Li 2 CO 3 , the sintering temperature of MN was further red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…For preparing single-phase Pb(Mg 1/3 Nb 2/3 )O 3 [3,4], MN shows better character than MgNb 2 O 6 [5,6]. Much attention has been paid to the fabrication of MN single crystal [7], luminescent properties and microwave dielectric properties of MN ceramic [1,2,8,9]. Usually, MN powders are synthesized by the conventional ball-milling method [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…For preparing single-phase Pb(Mg 1/3 Nb 2/3 )O 3 [3,4], MN shows better character than MgNb 2 O 6 [5,6]. Much attention has been paid to the fabrication of MN single crystal [7], luminescent properties and microwave dielectric properties of MN ceramic [1,2,8,9]. Usually, MN powders are synthesized by the conventional ball-milling method [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, borate ceramics have received substantial attention in recent years owing to their low raw prices, variable chemical structures, excellent dielectric properties, and straightforward preparation processes. Liu et al [12] reported that LiMBO 3 (M = Ca, Sr) ceramics could be densified at 800 • C with excellent dielectric properties (ε r = 8.7, Q × f = 75,000 GHz, and τ f = −150 ppm/ • C and ε r = 8.6, Q × f = 60,000 GHz, and τ f = −39 ppm/ • C) and could be chemically compatible with Ag. Zhou et al [13] prepared dense Li 6 B 4 O 9 microwave dielectric ceramics at 640 properties of ε r = 5.95, Q × f = 41,800 GHz, and τ f = −72 ppm/ • C, and a prototype patch antenna was fabricated by exploiting the compatibility of Li 6 B 4 O 9 with silver metallization using LTCC technology.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of Li 2 CO 3 and V 2 O 5 has been reported as a good fiux former to lower the sintering temperature for many materials [8,9]. The authors reported that the 3.0wt% Li 2 CO 3 -V 2 O 5 doped Mg 4 Nb 2 O 9 ceramic could be well sintered at 925 o C, while maintaining good dielectric properties [10]. Therefore, the effects of Li 2 CO 3 -V 2 O 5 combination addition as a sintering aids on the sintering behavior, microstructure and microwave dielectric properties of Mg 4 Nb 2 O 9 -CaTiO 3 composite ceramics were investigated.…”
Section: Introductionmentioning
confidence: 99%